A New Floating Memristance Simulator Circuit Based on Second Generation Current Conveyor - Cam, Zehra Gulru; Sedef, Herman (WORLD SCIENTIFIC PUBL CO PTE LTD, 2017)
In this paper, a new floating analog memristance simulator circuit based on second generation current conveyors and passive elements is proposed. Theoretical derivations are presented which decribe the circuit characteristics. The hardware of proposed simulator circuit is built using commercially available components. Theoretical derivations are validated with PSPICE simulation and experimental results. Performance of circuit was tested with simple example circuits. All results show that proposed simulator circuit provides frequency dependent pinched hysteresis loop and nonvolatility features. Exciting frequency, minimum and maximum memristance values and memristance range can be adjustable with simple passive element values. Simulator circuit has a frequency range of 1Hz to 40 kHz.
Keywords: Memristor; simulator; nonlinear resistor; current conveyor; current feedback operational amplifier; EMULATOR CIRCUIT; Computer Science; Engineering